Application of the SWAT Model and GIS to Assess the Impact of Land cover Change on Discharge and Sediment Load in the Srepok River Basin, Vietnam - Thi Bich, Nguyen; Viet, Nguyen Vu; Anh, Luu The; Thuy, Nguyen Thi; Thang, Nguyen Ngoc; Thanh Binh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 1DO - 10.25073/2588-1094/vnuees.5383, 2026)
The Srepok River Basin is part of the major river system in the Central Highlands, playing a crucial role in irrigation, hydropower generation, and sustaining cross-border flows to Cambodia. In recent years, the basin has been strongly affected by land cover changes and land use conversion, which have altered flow regimes and increased erosion and sedimentation. This study applied the SWAT (Soil and Water Assessment Tool) model in combination with a geographic information system (GIS) to simulate discharge and sediment in the Srepok River Basin, aiming to assess the impacts of land cover change on hydrological processes during 2010-2020. The results indicate that surface runoff in 2020 increased compared to 2010 (Ban Don station: +9.1%; Cau 14: +7.21%; Giang Son: +5.33%; Duc Xuyen: +6.67%). In contrast, baseflow decreased over the same period (Ban Don: -21.65%; Cau 14: -15.68%; Giang Son: -16.59%; Duc Xuyen: -17.69%). Sediment load also rose markedly in 2020 relative to 2010 (Ban Don: +8.5%; Giang Son: +4.65%). The main driver of these changes was the reduction in forest cover, which increased erosion and sediment load in the river. Overall, the results demonstrate that integrating the SWAT model with GIS is an effective approach for assessing the impacts of land cover change on discharge and sediment dynamics in the Srepok River Basin. The findings provide a scientific basis for basin management, land use planning, and sustainable utilization of natural resources, while supporting socio-economic development goals.